PENERAPAN PENDIDIKAN KARAKTER DAN NILAI-NILAI MORAL DALAM BAB AL-JAMI KITAB BULUGHUL MARAM KARYA IBNU HAJAR AL-ASQALANI : (Studi di Pondok Pesantren Darul Hikmah Kecamatan Bareng Jombang) - Khoirur Rozikin, Hari; Shofiyul Himami , Ahmad; Maskhuroh, Lailatul; Subki Mashadi, Ahmad (ILJ: Islamic Learning Journal, 2023)
Character education in the school environment is very important and a very basic thing to implement in schools because it optimizes the character of children who are starting to fade. Darul Hikmah Islamic Boarding School is one of the Islamic boarding schools in the Bareng sub-district, Jombang Regency, especially in the Jlopo hamlet, Tebel village. From the results of the location survey, the researchers found that students had good moral habits and behavior in the religious field, but there were a small number of them who did not reflect the character of the students. So the authors are interested in researching the application of character education and moral values ??in the Hadith of the BookBulughul Maram Work by Ibn Hajar Al-Asqalani at the Darul Hikmah Islamic boarding school with Jombang. This research method uses a qualitative approach, in collecting data using observation, documentation, and interview methods. While the data analysis technique uses a case study analysis technique. The result of this research is the application of character education and moral values ??in the Hadith of the BookBulughul Maram There are three types of work by Ibn Hajar Al-Asqalani at the Darul Hikmah Islamic boarding school with Jombang, namely:halaqoh, exemplary, habituation. The moral values ??applied at the Darul Hikmah Bareng Jombang Islamic boarding school are habituation, exemplary, religious, honest, disciplined, responsible, and caring.